Effect Of Supply Chin Product Quality Prima Service Costumer Satisfaction And Loyality - Indyah Hartami Santi; Indria Guntarayana (Jurnal Perilaku dan Strategi Bisnis, 2020)
This study aims to study and explain the relationships and independent variables, namely the variables Role Chain, Product Quality, Excellent Service on Customer Satisfaction and Loyalty. In this study using a mixed methods strategy using SEM Smart PLS analysis and qualitative in the derming cycle model priority concurrent triangulation strategy is the collection of qualitative data at the same time with research, then, comparing qualitative data with quantitative data to match the combination. The results of this study prove that the Research Regarding Product Quality. Assistance Chain for Customer Satisfaction. Help Chain for Customer Loyalty. Product Quality that impacts Excellent Service. Product Quality aimed at Customer Satisfaction. Product Quality that counts towards Customer Loyalty. Excellent Service To Customer Satisfaction. Excellent Service is valued towards Customer Loyalty. Customer Satisfaction Supports Customer Loyalty.